Modeling and control for generator in aerospace applications - Yeo, Alex Beng Keong (2016)
The trend of using electrical machine in aerospace applications had drastically increased due to several reasons over the years. However, the driving of the electrical machines using a two-level inverter would create undesirable consequences namely high current ripple, EMI problems and also high power losses. Hence, the objective of this project is to assess and evaluate a suitable converter topology for future embedded starter or generator taking in considerations of the mentioned consequences and requirements by carrying out a trade study. This paper will talk about the method of using a Digital Signal Controller (DSC) TMS320F28335 for producing signals to model and simulate the embedded electrical machine with the power converter and the development of control algorithms to process and thereafter produce 6 enhanced pulse width modulator (EPWM) signals which correspond to a sine wave signal from a DC source by varying of the duty cycle of the signals. The 6 distinct signals will correspond to a three phase system with the usage of complementary pair signals. Result and discussions with recommendations for future works are also presented at the end of the report.